A hybrid heuristic for inventory routing problem. (17th October 2011) - Ramkumar, N.; Subramanian, P.; Narendran, T.T.; Ganesh, K.
This paper addresses an inventory routing problem in vendor managed inventory systems with explicit consideration of buffer stock levels at warehouses. The problem involves a manufacturer delivering a product to a set of warehouses with available fleet capacity with the objective of minimising transportation and inventory costs. We have developed an integer linear programme (ILP) and proposed a hybrid heuristic for the problem. In the proposed heuristic, inventory is allocated using an ILP, vehicles are allotted to customers on the basis of proximity and routes for vehicles are determined using simulated annealing. The proposed heuristic is validated with different datasets and found to be performing well.